2017
DOI: 10.1111/aos.13646
|View full text |Cite
|
Sign up to set email alerts
|

Presenting characteristics and prevalence of polypoidal choroidal vasculopathy in Scandinavian patients with treatment‐naïve exudative age‐related macular degeneration

Abstract: Polypoidal choroidal vasculopathy (PCV) is not a rare condition in Danes with exudative AMD and presents often extramacular and with haemorrhage. This study underscores the importance of ICGA as a part of the diagnostic repertoire in AMD and suggests its routine use in Scandinavian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…We recently reported that when cases with PCV are stratified by their angiographic subtype (strong versus weak presence of BVN (Lorentzen et al. )), we observe differences in the immunologic profile of circulating monocytes (Subhi et al. ).…”
Section: Discussionmentioning
confidence: 91%
“…We recently reported that when cases with PCV are stratified by their angiographic subtype (strong versus weak presence of BVN (Lorentzen et al. )), we observe differences in the immunologic profile of circulating monocytes (Subhi et al. ).…”
Section: Discussionmentioning
confidence: 91%
“…; Lorentzen et al. , ). Although no studies have reported a higher NLR in patients with polypoidal choroidal vasculopathy, studies have found immunological differences between neovascular AMD and polypoidal choroidal vasculopathy (Subhi et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Lorentzen et al. ). The main characteristic of PCV is a branching vascular network (BVN) of Type 1 CNV with one or more aneurysmatic dilations (Yannuzzi et al.…”
Section: Discussionmentioning
confidence: 98%